Beliefs about being an English Teacher: hopes and fears - de Lima, Fernando Silvério (BELT - Brazilian English Language Teaching Journal, 2011)
Language teacher education is a complex process with several challenges for both sides. In this paper I make an option for the analysis of the future teachers’ side (undergraduates). This is a qualitative inquiry carried out in an English language discipline with Letters undergraduates. Through activities with movies I discussed aspects of language teacher education based on beliefs, expectations, challenges and fears that these teachers idealize in the future profession. The data analysis shows that the future teachers are insecure, some fears related to students (indifference and indiscipline), contextual factors and teacher fluency, but at the same time positive beliefs about themselves as future professionals.